The impact of family income on child achievement - Dahl, Gordon B. 1968-; Lochner, Lance (National Bureau of Economic Research, 2005)
"Understanding the consequences of growing up poor for a child's well-being is an important research question, but one that is difficult to answer due to the potential endogeneity of family income. Past estimates of the effect of family income on child development have often been plagued by omitted variable bias and measurement error. In this paper, we use a fixed effect instrumental variables strategy to estimate the causal effect of income on children's math and reading achievement. Our primary source of identification comes from the large, non-linear changes in the Earned Income Tax Credit (EITC) over the last two decades. The largest of these changes increased family income by as much as 20%, or approximately
Keywords: Erziehung; Academic achievement -- Economic aspects -- United States; Education -- Economic aspects -- United States; Poor children -- Education -- United States; USA